Evaluation of the 3D Topographic Effect of Homogeneous and Inhomogeneous Media on the Results of 2D Inversion of Electrical Resistivity Tomography Data. (15th February 2022) - Turarova, Marzhan Kabdykalievna; Mirgalikyzy, Tolkyn; Mukanova, Balgaisha Gafurovna; Modin, Igor Nikolaevich; Kaznacheev, Pavel Aleksandrovich
Abstract : This work is devoted to the creation of numerical 3D models for studying 3D topographic effects of homogeneous and inhomogeneous media on the results of 2D inversion. To solve the direct problem, the integral equations method (IEM) was applied to simulate the electric field and calculate the values of apparent resistivity. For the numerical solution of the integral equation, a computational mesh, adapted to the terrain features, was constructed. The calculation of the apparent resistivity of the medium was implemented for a pole-dipole array. Calculations have been performed for a conducting medium with 3D local inhomogeneity and the ground surface topography. The influence of the 3D model with topography, flat ground surface, and immersed inhomogeneity on the results of 2D inversion was estimated. Influencing factors of the 3D model, such as the slope angle of the topography, the resistivity ratio of the inhomogeneity and the host medium, the average size of inhomogeneity and topography, the distance from the inhomogeneity to the measuring line for the medium with and without topography, and the distance between the electrodes of the electrical resistivity tomography (ERT) array, were studied. Based on the research results, recommendations and conclusions that can be useful when conducting geophysical studies by the ERT method are drawn.